Photovoltaic Efficiency of Transition Metal Dichalcogenides Thin Films by Ab Initio Excited-State Methods - Marinho, Enesio [UNESP]; Villegas, Cesar E. P.; Venezuela, Pedro; Rocha, Alexandre R. [UNESP] (American Chemical Society (ACS), 2024)
Transition metal dichalcogenides (TMDCs) have garnered significant interest in optoelectronics, owing to their scalability and thickness-dependent electrical and optical properties. In particular, thin films of TMDCs can be used in photovoltaic devices. In this work, we employ ab initio many-body perturbation theory within the G0W0-BSE approach to accurately compute the optoelectronic properties of thin films of 2H-TMDCs composed of Mo, W, S, and Se. Subsequently, we evaluate their photovoltaic performance, including exciton recombination effects, and show that this is a key ingredient. We obtain efficiencies of up to 29% for a 200 nm thick film of WSe2, thus providing an upper limit. We also include other phenomenological recombination mechanisms that could be present in the current samples. This slightly reduces efficiencies, indicating that even with current synthesis technologies, there is still potential for further enhancement of TMDCs’ performance in photovoltaic applications.
Keywords: GW-BSE; MBPT; optoelectronics; photovoltaic efficiency; thin films; transition metal dichalcogenides